How Do the Electrical Properties of Graphene Change with its Functionalization?. Issue 3 (21st November 2012) - Sreeprasad, T. S.; Berry, Vikas
Abstract Functionalization of graphene is essential to interface it with other moieties to expand the scope of its electrical/electronic applications. However, chemical functionalization and/or molecular interactions on graphene sensitively modulate its electrical properties. To evaluate and take advantage of the properties of functionalized graphene, it is important to understand how its electrical attributes (such as carrier scattering, carrier concentration, charge polarity, quantum‐capacitance enhanced doping, energy levels, transport mechanisms, and orbital hybridization of energy‐bands) are influenced by a change in carbon's structural conformation, hybridization state, chemical potential, local energy levels, and dopant/interface coupling induced via functionalization or molecular interactions. Here, a detailed and integrated model describes factors influencing these electrical characteristics of functionalized graphene (covalent bonds, adsorption, π–π bonds, and lattice incorporation). The electrical properties are governed via three mechanisms: (a) conversion of carbon's hybridized state, (b) dipole interactions enhanced via quantum capacitance, and (c) orbital hybridization with an interfacing molecule. A few graphenic materials are also identified where further studies are essential to understand the effect of their functionalization.